The effects of audio-visual perceptual characteristics on environmental health of pedestrian streets with traffic noise: A case study in Dalian, China - Ren, Xinxin; Wei, Peng; Wang, Qiran; Sun, Wei; Yuan, Minmin; Shao, Shegang; Zhu, Dandan; Xue, Yishan (Frontiers in Psychology, 2023)
The COVID-19 pandemic has affected city dwellers’ physical and mental health and has raised concerns about the health of urban public spaces. This field investigation research in Dalian, China, examined the perceived audio-visual environment characteristics of urban pedestrian streets with traffic noise and their influences on the environmental psychology responses to health evaluations. The results showed that safety was rated the highest, and willingness to walk was evaluated as the lowest among health evaluation indicators. These indicators included willingness to walk, relaxation, safety, beauty, and comprehensive comfort. The imageability and openness of the streetscape were strongly associated with each health evaluation indicator. In contrast, the rhythm and continuity of the street buildings had a greater effect on willingness to walk than the other health indicators. There were negative correlations between LAeq for traffic noise and health evaluations. Positive health evaluations were observed when LAeq was less than 55 dBA. In contrast, soundscape indicators showed stronger correlations with health evaluations than LAeq; willingness to walk, relaxation, and comprehensive comfort were more affected than other health indicators. In terms of the combined audio-visual factors, acoustic comfort, the quantity of greening, sound annoyance, sky visibility, spatial scale, and building distance were examined as the determining factors affecting health evaluations, and 55.40% of the variance in health evaluations were explained by the soundscape and streetscape indicators. The findings provide references for better understanding the relationships between healthy experience and audio-visual perceptions and the health quality optimisation of pedestrian spaces considering audio-visual approaches in the post-epidemic era.